Exploration and molecular identification of proteolytic bacteria from rusip pacific oyster (Crassostrea gigas) as anticoagulant agent candidates - Afriansyah, Muhammad Ardi; Sudarwin; Dewi, Sri Sinto; Akbar, Gusti Dimas Refian (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2025)
The marine symbiont Staphylococcus epidermidis strain CGF-6, a protease-producing bacterium, has been successfully isolated from Rusip Pacific Oyster (Crassostrea gigas). S. epidermidis is a non-spore-forming, Gram-positive coccus commonly found in marine environments due to their ability to tolerate high salinity. The aim of this study was to identify proteolytic bacteria from Rusip fermented C. gigas as potential candidates for the development of anticoagulant agents. Bacterial isolation was performed through the fermentation process of Rusip. After seven days, bacterial colonies were purified three times using Nutrient Agar. The selection of proteolytic bacterial was conducted qualitatively using a skim milk agar medium. The bacterial isolates exhibiting the highest protease activity were identified through 16S rRNA gene sequencing using universal primers Bact 27F and UniB 1492R. Phylogenetic tree analysis, conducted with the MEGA X program, helped determine the relationships between species. Out of the 18 bacterial isolates obtained from the Rusip fermentation of C. gigas, three isolates (CGF-1, CGF-6, and CGF-11) exhibited hydrolysis zones around their colonies on skim milk agar, indicating protease activity.  Among these, isolate CGF-6 showed the highest proteolytic index of 0.5 and was identified as Staphylococcus epidermidis strain CGF-6. S. epidermidis strain CGF-6 has the potential to serve as a valuable source of protease production for the development of anticoagulant agents. However, further studies, including enzyme characterisation, optimisation, and both in vitro and in vivo anticoagulant activity tests, are necessary to assess the efficacy and safety of this enzyme as a candidate for anticoagulant agents.